Decentralization and Farmers’ Welfare in Indonesia - Sulanjari, Asterini (FIA UB, 2016)
This study examines the correlation between decentralization and farmers’ welfare uses quantitative design data from 2004-2013 from 32 provinces of Indonesia. The hypothesis is decentralization improves farmers’ welfare. The finding shows that DAU and PPL maintain a correlation with farmers’ welfare, while the history of local elections does not have any correlation. DAU has a positive correlation, while the number of PPL have a negative correlation. These findings suggest that welfare of farmers only have relationship with fiscal decentralization, or it can be said that farmers’ welfare increase through more DAU.